Dissipation pattern and dietary risk assessment of some commonly used insecticides on tomato (Solanum lycopersicum L.). (29th March 2022) - Singh, Shubhra; Dubey, Jatiender Kumar; Katna, Sapna; Sharma, Ajay; Devi, Nisha; Brar, Gaganpreet Singh; Singh, Gagandeep; Gautam, Himani; Thakur, Nimisha
Abstract: Pesticide residue in food commodities is a serious concern in relation to consumer safety and also the most significant barrier in the trade of food commodities. The dissipation pattern of four insecticides, namely novaluron, λ‐cyhalothrin, imidacloprid, and fenazaquin, was evaluated on tomato fruits and cropped soil. The residues were extracted using the QuEChERS analytical method and quantized using a gas chromatograph with electron capture detector, gas chromatograph mass spectrometer, and high‐performance liquid chromatography with photo diode array detector. The analytical method was validated using parameters like recovery, linearity, accuracy, matrix effect, and specificity, with limit of detection and limit of quantitation established to be 0.01 and 0.05 mg/kg, respectively, for all the pesticides. The average initial deposits (samples collected after 2 h of application) at the recommended dose of novaluron, λ‐cyhalothrin, imidacloprid, and fenazaquin were 0.593, 0.293, 0.227, and 0.431 mg/kg on tomato fruits, respectively, and were below the limit of quantification in soil. The pre‐harvest interval of 17, 8, 1, and 13 days was suggested for novaluron, λ‐cyhalothrin, imidacloprid, and fenazaquin on tomato, respectively. Risk assessment studies revealed that all pesticides under study are safe and do not pose any threat to humans as theoretical maximum dietary intake is less than the maximum permissible intake and acceptable daily intake.